2022
DOI: 10.1017/s1049023x22001297
|View full text |Cite
|
Sign up to set email alerts
|

Video Emergency Calls in Medical Dispatching: A Scoping Review

Abstract: Background: Video emergency calls (VCs) represent a feasible future trend in medical dispatching. Acceptance among callers and dispatchers seems to be good. Indications, potential problems, limitations, and directions of research of adding a live video from smartphones to an emergency call have not been reviewed outside the context of out-of-hospital cardiac arrest (OHCA). Objective: The main objective of this study is to examine the scope and nature of research publications on the topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…As in the Danish study, the causes of failure or difficulties were mainly related to the users’ handling of the smartphones or non-receipt/difficulty in accessing the SMS URL link. As with all published studies on the subject [ 17 , 27 , 28 , 30 ], acceptance of the video was excellent by both callers and physicians and was also considered easy to use.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…As in the Danish study, the causes of failure or difficulties were mainly related to the users’ handling of the smartphones or non-receipt/difficulty in accessing the SMS URL link. As with all published studies on the subject [ 17 , 27 , 28 , 30 ], acceptance of the video was excellent by both callers and physicians and was also considered easy to use.…”
Section: Discussionmentioning
confidence: 57%
“…The skills available and the assessment tools used in EMCCs should be adapted to the condition of the patients assessed. Medical skills and tools for live video are needed for patients requiring an ambulance, but also for low acuity situations [ 16 , 17 , 27 , 30 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several challenges regarding videocalls have been identified. 11 In the data material, operators attempted to use video without success in only five cases. This is lower than Bell et al 7 who found that video was not feasible in 40% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The skills available and the assessment tools used in EMCCs should be adapted to the condition of the patients assessed. Medical skills and tools for live video are needed for patients requiring an ambulance, but also for low acuity situations [16,17,27,30,34].…”
Section: Discussionmentioning
confidence: 99%